Effect of Community-Based Occupational Therapy on Health-Related Quality of Life and Engagement in Meaningful Activities of Women with Breast Cancer - Daiva Petruseviciene; Deive Surmaitiene; Daiva Baltaduoniene; Egle Lendraitiene (Occupational Therapy International)
We aimed to evaluate the short-term effects of community-based occupational therapy on health-related quality of life and engagement in meaningful activities among women with breast cancer. An open label randomized controlled trial study design was applied. The participants were members of various societies of women with cancer. In total, 22 women have participated in the study. Participants of the experimental group (n=11) participated in a 6-week community-based occupational therapy program and the usual activities of various societies, whereas the control group (n=11) women participated in the usual activities of the societies only. 1 of the participants withdrew during the course; therefore 21 completed the study successfully. Participants of both groups were assessed for health-related quality of life and the participants of the experimental group were assessed for engagement in meaningful activities. The evaluation was carried out during the nonacute period of the disease—at the beginning of the study and after 6 weeks. Women of the experimental group demonstrated statistically significantly better scores in the global quality of life, role functions, physical, emotional, cognitive, and social functions, fatigue, insomnia, financial impact, systemic therapy side effects, and breast symptoms scales compared to the control group participants (p<0.05) after the 6 weeks, as measured by the EORTC QLQ-C30 questionnaire and its breast cancer module QLQ-BR23. Furthermore, women of the experimental group demonstrated significant greater engagement in meaningful activities when applying community-based occupational therapy (p<0.05), as measured by using the Engagement in Meaningful Activities Survey (EMAS). The evaluation of the associations between the women’s engagement in meaningful activities and changes in health-related quality of life showed that greater engagement in meaningful activities was associated with better emotional functions and a lower level of insomnia (p<0.05). Based on the results of our study, we recommend applying occupational therapy in the field of community healthcare in order to maintain or improve breast cancer patients’ health-related quality of life and suggest involving women into meaningful activities during community-based occupational therapy after clarifying which activities are important to them.